Unsung heroes of the Dachau trials : the investigative work of the U.S. Army 7708 War Crimes Group, 1945-1947 - Dunphy, John J. 1953- (McFarland & Company, Inc., Publishers, 2019)
Klappentext: The U.S. Army 7708 War Crimes Group investigated atrocities committed in Germany and Nazi-occupied Europe during World War II. These young Americans-many barely out of their teens-gathered evidence, interviewed witnesses, apprehended suspects and prosecuted defendants at trials held at Dachau. Their work often put them in harm's way-some suspects facing arrest preferred to shoot it out.The WCG successfully prosecuted the perpetrators of the Malmedy Massacre, in which 84 American prisoners of war were shot by their German captors, and Waffen-SS commando Otto Skorzeny, aptly described as "the most dangerous man in Europe." Operation Paperclip, however, placed some war criminals-scientists and engineers recruited by the U.S. government-beyond their reach. From the ruins of the Third Reich arose a Nazi underground that preyed on Americans - especially members of the WCG.